Development and recommendation of kinematic event detection methods for use during bend sprint running - White, J.; Wilson, C.; Irwin, G.; von Lieres und Wilkau, H.; Moore, J.; Exell, T. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
This study aimed to validate different kinematic event detection methods for use during maximal velocity bend sprint running. Eight sprinters completed nine 60 m bend sprints each around an athletic track with a 36.5 m bend radius. Three kinematic event detection methods were adapted and compared to instances of touchdown and toe-off as determined by force plates. Using peak and maximum vertical acceleration of the toe marker yielded mean errors of less than 1 frame (0.004 s) for touchdown, whilst peak acceleration was the most accurate for determining toe off (mean error = 0.85 frame).The findings suggest that, when carefully applied with additional controls, kinematic-based event detection methods offer an accurate alternative to force-plate detection methods for use during biomechanical analyses of bend sprint running when ground reaction force data are not available.